1987
DOI: 10.1017/s0033291700013027
|View full text |Cite
|
Sign up to set email alerts
|

Mass hysteria: two syndromes?

Abstract: SynopsisOn the basis of a literature review it is concluded that mass hysteria can be divided into two syndromes. One form, to be called ‘mass anxiety hysteria’, consists of episodes of acute anxiety, occurring mainly in schoolchildren. Prior tension is absent and the rapid spread is by visual contact. Treatment consists of separating the participants and the prognosis is good. The second form, to be called ‘mass motor hysteria’, consists of abnormalities in motor behaviour. It occurs in any age group and prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
1
5

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 68 publications
2
59
1
5
Order By: Relevance
“…It has been described in humans as "very similar to a stampede in the animal world" (3, p. 301). It has also been called a culture-bound stress reaction (4), in which two separate mechanisms are at work: an anxiety variant, in which abdominal pain, headache, dizziness, fainting, nausea, and hyperventilation are the most common symptoms, and the motor variant, with common symptoms of hysterical dancing, convulsions, laughing, and pseudoseizures (5,6). Although it has been proposed that in modern Western society the "more primitive" motor variant essentially has been replaced in form by the anxiety variant (7), examples of this motor variant continue to be reported (8).…”
Section: Introductionmentioning
confidence: 99%
“…It has been described in humans as "very similar to a stampede in the animal world" (3, p. 301). It has also been called a culture-bound stress reaction (4), in which two separate mechanisms are at work: an anxiety variant, in which abdominal pain, headache, dizziness, fainting, nausea, and hyperventilation are the most common symptoms, and the motor variant, with common symptoms of hysterical dancing, convulsions, laughing, and pseudoseizures (5,6). Although it has been proposed that in modern Western society the "more primitive" motor variant essentially has been replaced in form by the anxiety variant (7), examples of this motor variant continue to be reported (8).…”
Section: Introductionmentioning
confidence: 99%
“…But in one of his papers, Small and Nicholi [13] think that the forthcoming expected loss of the school principal might have been abreacted in the outbreak. In some outbreaks, it looks like children's duplication of a larger social problem 1 We are not referring here to Wesseley's [59] distinction between two syndromes of epidemic hysteria differentiated on the basis of symptomatic patterns, the mass motor type and the anxiety hysteria type. We have seen in the analysis of the symptom profile of the outbreaks that this distinction is borne out as two poles of the symptomatic configuration.…”
Section: Discussionmentioning
confidence: 99%
“…Gruenberg (1957) hypothesised that social integration may play a role in developing social shared psychopathology. Wessely (1987) suggested that mass hysteria can be sub-divided into two varieties: mass anxiety hysteria and mass motor hysteria. Mass anxiety hysteria consists of episodes of acute anxiety seen generally in schoolchildren.…”
mentioning
confidence: 99%
“…On the contrary, mass motor hysteria shows abnormalities in motor systems which can be seen across all ages. Wessely (1987) points out that such type of motor hysteria may have a gradual spread. Whereas abnormality is confined to group interaction in mass anxiety hysteria, in mass motor hysteria abnormal personalities and environments are implicated.…”
mentioning
confidence: 99%